Mengelola Produktivitas Kerja - Aswaruddin Aswaruddin; Filma Muhazri Sembiring; Maulida Tri Puspita; Salisa Afany; Dea Anisha; Khairul Azmi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Managing work productivity is an important process in achieving organizational success. In the era of globalization and intense competition, managing work productivity is becoming increasingly important. Organizations that are able to optimize their work productivity will have a significant competitive advantage. Therefore, a good understanding of the concepts and practices of work productivity management is very important for managers and organizational leaders. This research aims to discuss the importance of managing work productivity. This research uses a qualitative method, descriptive research type. The results of the research are that private companies and those in government will always try to improve the performance of their employees or workforce to produce productivity that is in line with the company's ideals, which always increases at all times.